1998
DOI: 10.1136/bmj.316.7141.1356
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of low back pain in general practice: a prospective study

Abstract: Objectives: To investigate the claim that 90% of episodes of low back pain that present to general practice have resolved within one month. Design: Prospective study of all adults consulting in general practice because of low back pain over 12 months with follow up at 1 week, 3 months, and 12 months after consultation. Setting: Two general practices in south Manchester. Subjects: 490 subjects (203 men, 287 women) aged 18-75 years. Main outcome measures: Proportion of patients who have ceased to consult with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
354
1
16

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 607 publications
(380 citation statements)
references
References 8 publications
9
354
1
16
Order By: Relevance
“…Von Korff and Saunders [87], have shown that the natural history [20], among workers of the general population [83], and among compensated workers [65]. Back pain is a recurrent condition, a characteristic that cross-sectional, dichotomous measures of returnto-work do not capture.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Von Korff and Saunders [87], have shown that the natural history [20], among workers of the general population [83], and among compensated workers [65]. Back pain is a recurrent condition, a characteristic that cross-sectional, dichotomous measures of returnto-work do not capture.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…A total of 149 individuals (75 men; 74 women) met the inclusion criteria of no self-reported current neck disorders (score on the Neck Disability Index (NDI) < 20% (Fairbank et al, 1980), pain on the visual analogue scale (VAS) ≤ 10 mm (Croft et al, 1998), and no recurrent neck or low back pain, inflammatory joint disease, or other systemic disease during the last three years; 10 of the recruited men were unable to attend the testing. The sample was filled with 34 individuals (employees and students from a university) to include at least 80 men and 80 women (20 individuals in each of the following age intervals: 25-34, 35-44, 45-54 and 55-64 years) .…”
Section: Neck-healthy Individualsmentioning
confidence: 99%
“…7 It appears that there are mixed research results for SMT, with Assendelft et al 25 reporting no evidence that any therapy including analgesics, exercises, physical therapy, back schools, and SMT is superior to the other. Many studies are citing statistics that reflect that LBP will resolve in about 6 weeks regardless of the treatment received, but Croft et al 26 showed how only 8% of patients with LBP consulted with the initial physician even though 75% continued to have complaints, which may cause a wrong assumption that the patient has recovered. The patient in this case had comorbidities of DISH and DDD that both may have contributed to his complaints of lower back pain.…”
Section: Discussionmentioning
confidence: 99%